Sistem Pemantauan Kualiti Air (PeKA) - Mohd Zin, Ahmad Haziq; Ismail, Suhaila; Mohd Yusop, Nurhafizah Moziyana; Ahmad, Siti Rohaidah (Academica Press Solutions, 2024)
Water is a fundamental element of life and a critical resource for ecosystems, agriculture, industry, and human consumption. Most of the water sources on this earth are not safe to use. A group of researchers from the Faculty of Civil Engineering have taken the initiative to treat water in Bukit Gemilang. Treated water is stored in a clean water storage tank before being distributed for use. However, there is still no system or device to ensure that the water stored in the storage tank is safe for use. Therefore, the Sistem Pemantauan Kualiti Air (PeKA) was developed to monitor and measure the quality of water stored in storage tanks. The PeKA system is based on IoT devices and the PeKA web. This IoT device is equipped with three types of sensors, namely TDS Sensor, pH Sensor, and Turbidity Sensor as a tool to measure the level of water quality that has been treated. The PeKA system is developed based on HTML and PHP for system interface development. C++ programming language is used to develop IoT devices while MySQL is used as a database for data storage. The prototype methodology is used for the development of the PeKA System. This is because IoT device prototypes need to be built first to make the system evaluation phase. This system can make it easier for users who are water treatment researchers to monitor and measure the level of water quality that has been treated. Among the advantages of this system is in terms of the administration of the system which is self-administered by the water treatment researchers, the web-based implementation of the PeKA System allows the system to be accessed online. Subsequently, users will receive a warning notification of extreme changes in water quality.